Sodium-rich metasomatism in the upper mantle: Implications of experiments on the pyrolite-Na2O-rich fluid system at 950°C, 20 kbar - Mcneil A.M.; Edgar A.D. (My University, 1987)
Sodium-rich metasomatism in the upper levels of the mantle has been modeled by reacting pyrolite with alkali-bearing HâO fluids containing minor COâ and concentrations of NaâO and NaâO + KâO (K/K + Na = 0.1) up to 4.0 g alkalies/10 g HâO at 20 kbar and 950Â°C. With increasing alkali concentration, the amounts of amphibole (pargasite-edenite) and olivine increase as orthopyroxene and clinopyroxene decrease. Amphiboles show progressive increases in Na (and K) and Si concentrations and decreases in Al and Ca concentrations suggesting the dominant substitution mechanism is (Na, K) + Si in equilibrium Al + Ca. These results and least squares mass balance calculations suggest the reaction of clinopyroxene + orthopyroxene + spinel produces amphibole + olivine. The present study suggest that up to 43 wt.% amphibole may be accommodated in pyrolite in the presence of NaâO-rich HâO-COâ fluids. This represents 0.8 wt.% HâO and 1.7 wt.% NaâO in the hydrated pyrolite composition and indicates the importance of sodium in determining the extent of metasomatism. Sodium also lowers the solidus temperature of pyrolite by more than 50Â°C over the HâO-saturated pyrolite system at 20 kbar.